Trials and tribulations: high-yielding varieties and small farmers in Bihar, circa 1970 - Bell, Clive (AWI discussion paper series, 2025)
This paper recounts an early attempt to promote the adoption of high-yielding varieties (HYVs) of rice and wheat by small farmers. The instrument was a package not only of inputs, extension advice and supervision, but also – addressing risk aversion – a guaranteed net revenue. The scheme was implemented by the newly-created Small Farmers’ Development Agency, a parastatal body. The paper examines how and why the scheme failed, and analyses the data yielded by the trials. The chief causes of its failure were a lack of incentives within the public sector and the Agency’s weakness within the larger administrative system. Despite all manner of difficulties, the participants in the trials obtained levels of valued added per acre thrice those of their contemporaries cultivating local varieties and crop yields from two-thirds to four-fifths of those achieved by their grand children’s cohort circa 2020.